THE REGULATION OF EMPLOYMENT IN THE LABOUR MARKET UKRAINE - Zelinskaya, H. O. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article deals with the issue of regulation of human resources in the labor market of Ukraine. The studies suggest that the situation in the Ukrainian labor market requires constant monitoring by the state. It is noted that regulation of employment and unemployment in the labor market should be the focus of attention at different levels of government, since the increase in employment leads to an improvement in the living standards of the population and helps to reduce tensions in the labor market. It is proved that the unemployment of the population is a threat to the security not only political, economic, but also social. It is found out that today Ukraine is developing according to the industrial model of economic development, which is characterized by an increase in the demand for highly qualified personnel, focus on their innovation and mobility. Despite this, the advanced countries of the world are moving to a post-industrial model of economic development. It is proved that the modern employment system still retains the characteristic features of an industrial model. It is emphasized that the characteristic features of the current state of the Ukrainian labor market are the imbalance between supply and demand, the education system does not meet the real needs of the labor market, which requires a highly qualified competitive worker. Special attention is paid to the issue of state regulation of employment and unemployment, in particular, it is indicated that the priority areas of state regulation of employment should be the implementation of economic policy in the interests of employment. It is determined that the state plays the role of a catalyst in the formation of social policy, and the development of human resources should become a strategic direction of the Development Programs of Ukraine. It is determined that in order to achieve the goal in the field of labor and rapid economic growth, in the conditions of population reduction, improvement of conditions and strengthen incentives for the formation of labor potential and its most effective use. It is determined that a flexible combination of state regulation and market self-government, especially now provides, on the one hand, the mitigation of the reform phase, and, on the other hand – an organized departure from centralized management to the social partnership of the state, employers and local authorities. It is recommended to introduce the model of economy with expensive labor force that will create conditions for decent work, self-realization of its citizens and decent life.